Perlindungan Hukum bagi Korban Kejahatan Penipuan - Muhammad Nasir; Johari Johari; T. Halimah; Phoenna Ath Thariq; Ummi Kalsum (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2022)
The arrangement on victims in the Kuhap is only stipulated in Article 98 to Article 101, the articles relate to the right of victims in demanding compensation. The mechanism taken is the merger of lawsuit cases in exchange for criminal cases. The purpose of this study is to explain the underlying importance of legal protection against victims of fraud crimes and forms of legal protection for victims of fraud crimes in the provisions of the Kuhap and RKUHAP. The research methods used in this study are: Normative type of juridical research. With a legal approach, and a conceptual approach. The victim is a party who is harmed in the occurrence of a crime so that it must get attention and service in providing protection against it. The importance of protection to create a just and peaceful society without any crime or violence. Article 133 RKUHAP is regulated on compensation for victims who state if the defendant is criminally convicted and there are victims who suffer material losses. For law enforcement officials to pay attention and prioritize justice in providing protection to victims because victims have suffered losses and mental disorders and the rule of law that has been made must be carried out and given in accordance with what has been determined.